(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Iron plays a vital role in the development of fetus. Requirements of nutrition are increased during pregnancy for proper fetal growth and development along with the change in maternal metabolism. Thus the study was undertaken to assess hemoglobin and serum iron level in the first trimester of pregnancy with aim to focus the needs for a sustainable strategy to improve maternal and fetal micronutrition to prevent the adverse pregnancy outcome. Materials and methods: This study was a hospital based cross sectional observational study comprising 100 pregnant women who were recruited during their first antenatal visit in the first trimester of pregnancy, while attending the Outdoor of Gynaecology and Obstetrics, Chittagong Medical College Hospital and 50 non-pregnant women as control. Serum iron and hemoglobin level were evaluated in the Department of Biochemistry, Chittagong Medical College. Results: In this study, of 100 cases, anaemia was detected (Hb<11gm/dl) in fifty- three (53% of cases) pregnant women. However, iron deficiency (S. iron<50µg/dl) was seen in forty-two (42% of cases) pregnant women. Haemoglobin level and serum iron were significantly decreased in pregnant women in first trimester than that of non-pregnant healthy women as p<0.05. There were no significant differences for age, BMI, parity, hypertension and diabetes mellitus with these levels. Low Hb% and serum iron were significantly associated with the low socioeconomic condition of cases. Hb% level was significantly higher in pregnant women with diabetes mellitus. Conclusion: This study may give baseline information to detect hidden iron deficiency in early pregnancy in developing countries like Bangladesh where nutritional deprivation is more prevalent. JCMCTA 2023 ; 34 (2) : 95-100